Full process evolution of deformation and seepage coupling in fractured rock under triaxial stress - Jilu Zhang; Xiaohan Zhou; Xinrong Liu; Lei Fang; Xueyan Guo; Hao Chen (Scientific Reports)
Abstract To forecast the release of hazardous gases during deep underground excavation, it is essential to understand how normal and lateral stresses interact to influence fracture surfaces in rock mass deformation and seepage development. This study investigates the complete stress–strain–seepage response of fractured rock under varying fracture angles and gas pressures through triaxial testing. Results show that gas pressure begins to significantly promote fracture opening when the gas-to-confining pressure ratio (p/σ 3) exceeds 7.5. However, increasing gas pressure has limited influence on the overall failure mechanism. As deviatoric stress increases, rock mass permeability initially decreases and then increases, with the enhancing effect growing at higher stress levels. A fracture permeability model incorporating lateral stress effects was developed to simulate the dynamic coupling of damage and seepage throughout loading and unloading. The model effectively captures the dynamic evolution of seepage under the coupled damage-deformation conditions by iterating damage and seepage computations. Simulations reveal that increased lateral stress reduces normal stress on fracture surfaces, with its influence becoming more pronounced as fracture angle decreases and gas pressure rises. Damage accumulation further reduces normal stress, significantly affecting gas flow at the inlet and rupture planes, while having minimal impact at the outlet. These findings offer valuable insights for predicting gas release during deep tunnel excavation.